Play and leisure in Australian School Age Care: Reconceptualizing children's waiting as a site of play and labour. (November 2019) - Hurst, Bruce
Australian School Age Care programmes are little researched childhood settings that are commonly understood as sites of leisure and play in between school and home. This article draws on recent research to consider the status of a seemingly non-playful activity, that of children's waiting in School Age Care. The poststructural framing in this article conceptualizes waiting as an activity that incorporates acts of emotional labour, play and identity construction. It prompts consideration of whether waiting is a site of play and should therefore be incorporated in programming practices in School Age Care and other play-based settings.